Cypriot teachers’ digital skills and attitudes towards AI - Maria Kasinidou; Styliani Kleanthoys; Jahna Otterbacher (Discover Education)
Abstract Artificial Intelligence (AI) is now everywhere, including in the classroom. Thus, it is crucial for teachers not only to be able to use AI, but also to understand it, as they bear the responsibility of teaching the next generation with and about AI. Although there have been extensive discussions about the importance of digital skills and knowledge of AI, limited research has focused on the attitudes, digital skills, and AI literacy levels of teachers, within small populations where English is not the native language, such as Cyprus. Our study addresses this gap by adapting the General Attitudes Towards AI Scale (GAAIS) and the AI Literacy Scale (AILS) into the Greek language, and investigating the digital skills, attitudes towards AI, AI literacy, and intentions to teach and use AI among teachers in Cyprus. The Greek versions of GAAIS and AILS have been validated, demonstrating good validity and reliability. Our findings also indicate that Cypriot teachers generally possess intermediate digital skills, but maintain neutral attitudes towards AI and exhibit intermediate levels of AI literacy. Moreover, we discovered significant positive correlations between teachers’ digital skills and their AI literacy, attitudes towards AI, and intentions to use and teach AI.